UJI pH DAN KARAKTER FISIK KUALITAS AIR DI PEMUKIMAN PABRIK KELAPA SAWIT (PKS) NAGA SAKTI TAPUNG HILIR - Lestari, Endang Susi; Wirman, Shabri Putra; Febriani, Noni; Suroso, Aji (Sistem Informasi, 2015)
Water is the source of life for all living beings on this earth. Some sources of water for daily needs comes from shallow wells, artesian wells, springs, surface water and rain water collection. The Naga Sakti cottage settlements is one of the settlements adjacent to the Palm Oil Mill (POM) in the district of Lower Tapung Riau Kampar district, and the location of settlements in the area of oil palm plantations. Water produced from wells on the settlement sometimes colored and taste. therefore necessary to test the water pH and physical to determine whether the water in the wells meet the Ministry of Health of the Republic of Indonesia Number: 416/MENKES/PER/IX/1990 about water quality requirements with a pH test and physical parameters that include viscosity, Total Dissolved solids (TDS), Density, conductivity, Oxidation Reduction Potential (ORP), resistivity, salinity, and taste test. Water quality testing was conducted at a radius of 4 km to 8 km from the MCC. From the results of the pH test has been done, there are three that are close to the standard radius PERMENKES ie a radius of 4, 5 and 6 miles. As for the 8 km radius pH values far below the standard Permenkes at pH test. Then to test all the physical radius PERMENKES already meet the standards , in the form of test viscosity, density, ORP, TDS, salinity, conductivity, resistivit , and flavor .